Plasminogen Levels in Healthy Volunteers -Influence of Age, Sex, Smoking and Oral Contraceptives - Tait, R C; Walker, Isobel D; Conkie, J A; Islam, S I A M; McCall, Frances; Mitchell, R; Davidson, J F (Thrombosis and Haemostasis, 1992)
There is considerable doubt as to the importance of reduced plasminogen (PLG) activity as a risk factor for venous thrombosis. In the present study we have identified a wide range of PLG activities (25–200%) in a cohort of 9,611 blood donors. Males and females not taking hormonal contraceptives show a similar distribution of PLG, however, variation related to age appears to follow a different pattern in males and females. These differences are of doubtful clinical importance as are differences related to smoking. In contrast, females taking hormonal contraceptives or hormone replacement therapy (HRT) have up to 25% higher mean PLG levels in younger females but a less marked elevation (10%) is seen in 40–50 year olds. A PLG activity <65% was recorded in 61 donors, none of whom appeared to have a history of thrombosis. These findings do not support the notion that reduced PLG is an important thrombophilic risk factor, however, further investigation of the donors with low PLG is required.